PAGINE D’ARCHIVIO. LA LETTERATURA ROMENA NEI PIANI EDITORIALI DELLA CASA UTET (Analele Universității București. Limba și literatură română, 2024)
Developed starting from some archive materials, this contribution intends to propose a first synthetic reconstruction of the interest shown by the editorial directors of the UTET publishing house towards Romanian literature. The papers preserved in the archive did not perhaps provide many details on the literary translations published in the well-known book series I Grandi Scrittori Stranieri, but they reveal some nineteenthand twentieth-century projects, “missed opportunities”, which, alongside the publications, allow us to better frame interests and editorial plans of the publishing house.